Radial acceleration and cumulation of ions by an intense converging ring laser pulse - Balakirev, V.A.; Onishchenko, I.N.; Povrozin, A.I.; Tolstoluzhsky, A.P.; Yegorov, A.M. (Вопросы атомной науки и техники, 2008)
Cumulation dynamics and acceleration of deuterium plasma ions by a focused ring laser pulse of the femtosecond duration are theoretically investigated. Laser pulse is focused by a dielectric lens. The spatial structure of ring laser pulse field in the vicinity of the lens focus is determined. The values of cumulation coefficient of ions, their energy, and cumulation region dimensions are obtained. Conclusions are made about the possibility of the neutron source elaboration on considered cumulation principle.